Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1128/iai.00890-12
|View full text |Cite
|
Sign up to set email alerts
|

TRIF Mediates Toll-Like Receptor 2-Dependent Inflammatory Responses to Borrelia burgdorferi

Abstract: TRIF is an adaptor molecule important in transducing signals from intracellularly signaling Toll-like receptor 3 (TLR3) and TLR4. Recently, TLR2 was found to signal from intracellular compartments. Using a synthetic ligand for TLR2/1 heterodimers, as well as Borrelia burgdorferi, which is a strong activator of TLR2/1, we found that TLR2 signaling can utilize TRIF. Unlike TRIF signaling by other TLRs, TLR2-mediated TRIF signaling is dependent on the presence of another adaptor molecule, MyD88. However, unlike M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 59 publications
2
74
2
1
Order By: Relevance
“…Induction of type I IFN production is one downstream effect of TLR stimulation. Previous studies have indicated roles for MyD88 and TRIF in the type I IFN response of bone marrow-derived macrophages following B. burgdorferi stimulation (40). Our data show, however, that the B. burgdorferi infection-induced B cell accumulation is dependent on type I IFNR signaling but independent of the major TLR adapter proteins MyD88 and TRIF (Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…Induction of type I IFN production is one downstream effect of TLR stimulation. Previous studies have indicated roles for MyD88 and TRIF in the type I IFN response of bone marrow-derived macrophages following B. burgdorferi stimulation (40). Our data show, however, that the B. burgdorferi infection-induced B cell accumulation is dependent on type I IFNR signaling but independent of the major TLR adapter proteins MyD88 and TRIF (Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…However, TLR2 has been shown to traffic to the endosomal membrane upon recognition of B. burgdorferi lipoproteins and contributes to MyD88/TRIF-dependent transcriptional activation of type I IFN gene products (28,48). Therefore, it was important to establish the potential contribution of TLR2-specific ligands to the type I IFN response we observed.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse bone marrow-derived macrophages, transcriptional activation of IFN-responsive genes occurs via an IRF3-dependent but MyD88-and TRIF-independent pathway following recognition of B. burgdorferi RNA and multiple proteins by an unidentified cytosolic receptor (12). Petnicki-Ocwieja and colleagues demonstrated that B. burgdorferi initiates IFNA and IFNB gene transcription in mouse macrophages through activation of endosomally localized TLR2 and contributions from both MyD88-and TRIF-dependent signaling pathways (28). These studies with isolated immune cell populations, while providing crucial mechanistic insights into the production of B. burgdorferi-induced type I IFNs by specific cell types, are limited by the fact that these observations may not fully reflect the immune response in vivo, which results from an intricate network of interactions among multiple cell types.…”
mentioning
confidence: 99%
“…We are currently delineating the underlying mechanism by which OspC affects phagocytosis by macrophage. In this regard, it is known that phagocytosis of B. burgdorferi by macrophages involves several phagocytic receptors (91)(92)(93) and pattern recognition receptors (28,94). One possibility is that OspC alters phagocytic receptor profiles upon contact with macrophages.…”
Section: Discussionmentioning
confidence: 99%